UPAYA MENINGKATKAN HASIL BELAJAR PASSING BAWAH DALAM PERMAINAN BOLA VOLI MINI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING SISWA KELAS VI SDN 222 GRESIK - Nurul Hidayat; Atmojo Prayogo Widodo; Vega Candra Dinata; Zurnita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to see and analyze the improvement of students' PJOK learning outcomes through the discovery learning model in Class VI SDN 222 Gresik in the odd semester of 2024/2025. This study was conducted using the Classroom Action Research method which consists of three cycles, where each cycle consists of; planning, action, observation and reflection. Implemented from January to September 2024. Data was processed in each cycle and then analyzed using a percentage. The results obtained from this study are that using the Discovery Learning model can improve students' PJOK learning outcomes. This is evident from the increase in student learning outcomes in each cycle. The conclusion obtained from this study is that the use of the Discovery Learning Model can improve student learning outcomes.